Appropriate radiation dose for symptomatic relief and local control in patients with adult T cell leukemia/lymphoma. (17th August 2018) - Maemoto, Hitoshi; Ariga, Takuro; Nakachi, Sawako; Toita, Takafumi; Hashimoto, Seiji; Heianna, Joichi; Shiina, Hideki; Kusada, Takeaki; Makino, Wataru; Kakinohana, Yasumasa; Miyagi, Takuya; Yamamoto, Yuichi; et al.
Abstract: Adult T-cell leukemia/lymphoma (ATL) is an aggressive peripheral T-cell neoplasm that occurs only in patients with human T-cell leukemia virus type 1. No large study or randomized trial investigating radiotherapy (RT) for ATL has been performed. We retrospectively reviewed 55 courses of RT for 41 consecutive patients with ATL who underwent RT between 2000 and 2016 at our institutions. The results showed that RT for local ATL lesions can achieve symptomatic improvement in 92% of cases. Local remission, either complete remission (CR) or partial response (PR), was achieved in 100% of the patients (CR: 89%, PR: 11%) with ≥40 Gy irradiation. CR or PR was achieved in 71% (CR: 29%, PR: 43%) with 30–39 Gy and in 73% (CR: 6.7%, PR: 67%) with ≤29 Gy irradiation. The mean total radiation dose in the CR and PR groups differed significantly (38 vs 25 Gy, P = 0.0002). The maximum acute toxicity was Grade 0–2 in all patients, except for one patient experienced Grade 3 radiation dermatitis. In-field relapses occurred in 36% of patients, and the frequency of in-field relapses was 11%, 30% and 71% among those who achieved CR, PR and SD, respectively. All 9 patients who received total skin irradiation experienced cutaneous relapses, with a median of 63 days (range, 7–210 days). Almost all (39 of 41) patients with ATL experienced out-of-field progression after RT. In conclusion, RT was confirmed to be effective and safe for palliative treatment of local ATL lesions.